Food politics and activist networks in the city: reaching places food and policies don't - Trombini, Maria Eugenia; Campos Motta, Renata (Cities, 2025)
According to scholarship on the state-society relations that inform food and urban politics, social movements and civil society are key agents of change thanks to their ability to develop alternative food initiatives, organize networks, and influence public policies. Celebrated as a world pioneer in food governance and nutrition security, Belo Horizonte offers insight into the role played by activist networks, including institutional activism in food policies. Yet how can food politics connect alternative urban ecology aspirations with food justice in the city? In order to answer this question, we draw on focus groups with state actors and civil society organizations (CSOs) engaged in urban food systems since the 1990s to reveal the hybrid character of these initiatives, activist networks that transcend institutional boundaries, and broader socioecological transformation in the urban food system through agroecology. As the hunger crisis deepened during COVID-19, social movements and state actors devised initiatives to get fresh, ecological, nutritious, quality food to places it was not reaching in the city. Our investigation reveals, first, that over three decades, networks comprised of state actors and CSOs have played a key role in Belo Horizonte food policies and politics, connecting the peripheries with the core where public policies are made. However, food inequalities stemming from spatial segregation remain a challenge for more inclusive food policies. Second, by sampling participants who have been active in the city's food politics since the 1990s, our data shows the importance of tracing state-society networks over time, instead of focusing on critical moments of institutional building. Finally, the case of Belo Horizonte shows how local networks can influence public policies and actors at broader scales, even nationwide.